Stabilization of the Turkish Economy in the Early 2000s and the Urgent Action Plan - Seref Turkmen (European Scientific Journal, ESJ, 2023)
The first major crisis that the Justice and Development Party, which came to power in 2002, had to deal with was the deep social divisions caused by the 1990s, and especially the Ecevit era, and the near-bankruptcy of the Turkish economy. Without wishing to be exhaustive, it is worth highlighting some of the factors and events from this period in order to make visible how complex the crisis was that the AKP had to deal with while stabilizing Turkey after their first election victory. One of the reasons for the constant crisis of the 1990s was that the political scene was extremely polarized, many parties with relatively little influence were present in the National Assembly, and they were unable to secure a stable government majority. As a result, coalition governments were formed in which parties with very different ideologies participated. After a while, the army also intervened in the ongoing battles of the parties. In 1997, during the so-called the postmodern coup, the Turkish armed forces published an e-memorandum on the Internet. With this document, the government of the radical right-wing Necmettin Erbakan was finally overthrown. Between 1997 and 2002, there was a deeper political crisis compared to the previous years, it marked the repulsion of Turkish political life. The political crisis was further exacerbated by one of the greatest natural disasters of the republic’s era, the 1999 earthquake, which claimed tens of thousands of lives in the eastern basin of the Marmara Sea. The disaster, which had just ruined the developing hinterland of the country’s industry, slowed the businesses and the recovery exceeded the capabilities of the Turkish economy. After 1999, nearly one million small and medium-sized businesses went bankrupt. Not only companies, but also families were in an extremely difficult position with unemployment in the skies and inflation galloping. In this economic crisis, the pre-AKP Turkish governments resorted to the instrument of neoliberal economic policy. Kemal Dervis, an internationally known and recognized economist, was asked to create the economic recovery program. However, the extreme austerity measures provoked even more serious social tensions, which brought the long 1990s to the point where the last coalition government also failed. The present article aims at describing the nature of the economic crisis of 2001, and the forms of recovery used by Kemal Dervis and the subsequent AKP governments. Globally speaking, the economic crisis management was successful, so this paper –using both English and Turkish language sources- tries to clarify how the neo-liberals of the late Ecevit era and the liberals of the early AKP period contributed to this achievement.